Enhancing Social Inclusion through Subsidized Food Programs: Insights from Anies Baswedan's Leadership in Jakarta - Ikhsanto Fauzan Nur; Nurmandi Achmad; Fridayani Helen Dian (BIO Web of Conferences)
This study analyzes Anies Baswedan's leadership role in promoting social inclusion through subsidized food programs. This research uses descriptive qualitative methods with data collection techniques through literature studies and secondary data sources from official mass media reports. In line with the vision and objectives to lead and manage Jakarta with constructive transformation, the Provincial Government of DKI Jakarta implemented a subsidized food program to alleviate poverty and meet the population’s nutritional needs, especially the poor. The results showed that Anies Baswedan successfully implemented the subsidized food program with high efficiency and effectiveness, providing maximum benefits for the community. The program ensures that subsidized food remains affordable, thus increasing accessibility and equal opportunity for all citizens to participate and benefit. The impact of this program is not only to ease the burden of living, but also to improve the nutritional status of children and certain groups in Jakarta. Regular evaluations and monitoring are conducted to ensure the quality and safety of the subsidized food, with strict supervision of the distributed foodstuffs.